Model of public service satisfaction in PTKIN based on spirituality and islamic relational ethics - Nurhanifah; Hasnun Jauhari Ritonga; M. Agung Rahmadi; Helsa Nasution (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study investigates the public service model in State Islamic Higher Education Institutions (PTKIN) through the perspective of Islamic public relations communication by adopting a mixed-methods design that synthesizes evidence from a field survey (n=384 respondents from UIN Surabaya, UIN Malang, UIN Jakarta, and UIN Banten) and a meta-analysis of 47 published studies conducted during the 2018–2024 period. The Confirmatory Factor Analysis (CFA) results demonstrated a measurement model exhibiting an excellent level of goodness of fit (χ²/df = 2.184, CFI = 0.964, TLI = 0.958, RMSEA = 0.056, SRMR = 0.042). Furthermore, the findings reveal that service spirituality (factor loading=0.847, CR=0.912, AVE=0.675) and Islamic relational ethics (factor loading=0.823, CR=0.898, AVE=0.638) function as significant predictors of stakeholder satisfaction (β=0.514, p<0.001; β=0.398, p<0.001). Meta-analytic validation further substantiates these relationships, indicating aggregate effect sizes of r = 0.624 (95% CI: 0.587–0.658) for spirituality and r = 0.571 (95% CI: 0.531–0.609) for relational ethics. These findings corroborate the results while simultaneously establishing the novelty of the present study by demonstrating that the dimension of qaulan karima (β=0.287) exerts a stronger influence than qaulan layyina (β=0.219) within the context of PTKIN service delivery. The developed structural model accounts for 68.4% of the variance in service satisfaction, surpassing the 54.7%. The theoretical implications of this study reaffirm the relevance of the Service-Dominant Logic framework within Islamic Public Relations, wherein the dimensions of ta'awun and at-tasyir operate as distinctive cultural mediators within Indonesia's Islamic higher education ecosystem.